Kilas Balik Kebijakan Pendidikan Islam Indonesia pada Masa Orde Baru (1967-1997) - M. Syahran Jailani; Muhammad Muhammad (INNOVATIO: Journal for Religious Innovation Studies, 2019)
Islamic education during the New Order experienced a growth both quantitatively and in terms of the quality of the organization. The New Order policy in Islamic Education, for example: the government implemented Islamic religious education taught in elementary schools to higher education, madrasa institutions and pesantren began to be recognized, the provision of facilities and others. Government policies during the New Order era, although providing fresh air for the development of Islamic education, the stakeholders must fight and work hard to convince the government so that the existence of Islamic education remains recognized and has the same position with other education nationally.